Febrile Seizures and Febrile Seizure Syndromes: An Updated Overview of Old and Current Knowledge - Abdulhafeez M. Khair; Dalal Elmagrabi (Neurology Research International)
Febrile seizures are the most common paroxysmal episode during childhood, affecting up to one in 10 children. They are a major cause of emergency facility visits and a source of family distress and anxiety. Their etiology and pathophysiological pathways are being understood better over time; however, there is still more to learn. Genetic predisposition is thought to be a major contributor. Febrile seizures have been historically classified as benign; however, many emerging febrile seizure syndromes behave differently. The way in which human knowledge has evolved over the years in regard to febrile seizures has not been dealt with in depth in the current literature, up to our current knowledge. This review serves as a documentary of how scientists have explored febrile seizures, elaborating on the journey of knowledge as far as etiology, clinical features, approach, and treatment strategies are concerned. Although this review cannot cover all clinical aspects related to febrile seizures at the textbook level, we believe it can function as a quick summary of the past and current sources of knowledge for all varieties of febrile seizure types and syndromes.